Trade Therapy : Deepening Cooperation to Strengthen Pandemic Defenses - World Bank (Washington, DC : World Bank, 2022)
This report provides new data on trade in medical goods and services and medical value chains; surveys the evolving policy landscape before and during the pandemic; and proposes an action plan to improve trade policies and deepen international cooperation to deal with future pandemics.